Under the dome : a novel - King, Stephen, 1947- (New York : Scribner, 2009)
When the smalltown of Chester's Mill, Maine, is surrounded by an invisible force field, the people inside must exert themselves to survive. The situation deteriorates rapidly due to the dome's ecological effects and the machinations of Big Jim Rennie, an obscenely sanctimonious local politician and drug lord who likes the idea of having an isolated populace to dominate. Opposing him are footloose Iraq veteran Dale (3z(BBarbie(3y (BBarbara, newspaper editor Julia Shumway, a gaggle of teen skateboarders and others who want to solve the riddle of the dome.s
Includes author's note.
Keywords: Maine -- Fiction; Psychological fiction; Suspense fiction